Matching objects without language extension - Visser, Joost (2006)
Pattern matching is a powerful programming concept which has proven its merits in declarative programming. The absence of pattern-matching in object-oriented programming languages is felt especially when tackling source code processing problems. But existing proposals for pattern matching in such languages rely on language extension, which makes their adoption overly intrusive. We propose an approach to support pattern matching in mainstream object-oriented languages without language extension. In this approach, a pattern is a first-class entity, which can be created, be passed as argument, and receive method invocations, just like any other object. We demonstrate how our approach can be used in conjunction with existing parser generators to perform pattern matching on various kinds of abstract syntax representation. We elaborate our approach to include concrete syntax patterns, and mixing of patterns and visitors for the construction of sophisticated syntax tree traversals.